Preparation, Characterisation and Application of Metal-Doped Carbons for Hydrogen Cyanide Removal - P.A. Barnes; M.J. Chinn; E.A. Dawson; P.R. Norman (Adsorption Science & Technology)
A novel method for the production of metal-doped activated carbons was developed. Evaluation of the materials produced showed that the metals were well dispersed throughout the carbon pore structure and had a high degree of accessibility. The filtration performance of these materials was assessed against HCN using inverse gas chromatography. The performance was affected both by the selection of metals and the conditions used in the production of the carbon. In-depth studies varying the synthesis parameters were performed with the aim of optimising the manufacturing process. Significant HCN adsorption capacity was developed which exceeded that of the current best available ASC-type carbons.